Rethinking School Nutrition via Community Engagement: A Review with Implications for Indonesia’s MBG Program - Adnan Achiruddin Saleh; Suparman Abdullah; Rahmat Muhammad; Muhammad Yusran Amir; Sulvinajayanti Sulvinajayanti (Faculty of Public Health, Hasanuddin University, Makassar, 2025)
Community engagement has become a growing concern in the implementation of school nutrition programs, particularly in addressing issues of child malnutrition, food insecurity, and educational outcomes. However, definitions and levels of participation remain conceptually fragmented across various studies. This study aims to systematically review the scope, forms, and implications of community engagement in school-based nutrition programs. A Systematic Literature Review (SLR) was conducted on 89 Scopus-indexed publications from 1984 to 2025 using the PRISMA 2020 protocol. Thematic analysis was employed to identify the conceptual, methodological, and contextual variations of community involvement. Data were collected through document analysis of peer-reviewed journal articles focusing instead on qualitative synthesis. The study examined forms of engagement based on eight participation levels and five thematic domains. Results show that the relevance of the topic has increased significantly, especially in the last decade, with a marked rise in academic interest from diverse institutions. While collaborative practices such as cross-sector coordination, parental involvement, and grassroots food initiatives are often promoted, most programs operate at symbolic or consultative levels, rarely advancing to full empowerment. Contextual cases, such as Indonesia’s Free Nutritious Meals Program (MBG), illustrate both the promise and challenge of operationalizing community engagement at scale. This review concludes that future research must adopt a more theory-informed and practice-oriented approach to community participation, supported by clearer frameworks, inclusive governance models, and culturally adaptive implementation strategies.